2018
DOI: 10.1038/s41598-018-25150-z
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative SUMO proteomics reveals the modulation of several PML nuclear body associated proteins and an anti-senescence function of UBC9

Abstract: Several regulators of SUMOylation have been previously linked to senescence but most targets of this modification in senescent cells remain unidentified. Using a two-step purification of a modified SUMO3, we profiled the SUMO proteome of senescent cells in a site-specific manner. We identified 25 SUMO sites on 23 proteins that were significantly regulated during senescence. Of note, most of these proteins were PML nuclear body (PML-NB) associated, which correlates with the increased number and size of PML-NBs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 65 publications
2
23
0
Order By: Relevance
“…Therefore, non-SUMOylated PIAS1 can still localize, albeit less efficiently, to PML nuclear bodies via the SIM that is located on PIAS1 and the SUMOylated moieties on PML. A similar phenomenon was reported by our group for the SUMO E2 protein UBC9 34 . Taken together, these experiments confirmed that colocalization of PIAS1 at PML nuclear bodies is partly mediated by the SUMOylation of PIAS1 at Lys-137, Lys-238, and Lys-315 residues.…”
Section: Pias1 Overexpression Caused a Global Increase In Proteinsupporting
confidence: 88%
“…Therefore, non-SUMOylated PIAS1 can still localize, albeit less efficiently, to PML nuclear bodies via the SIM that is located on PIAS1 and the SUMOylated moieties on PML. A similar phenomenon was reported by our group for the SUMO E2 protein UBC9 34 . Taken together, these experiments confirmed that colocalization of PIAS1 at PML nuclear bodies is partly mediated by the SUMOylation of PIAS1 at Lys-137, Lys-238, and Lys-315 residues.…”
Section: Pias1 Overexpression Caused a Global Increase In Proteinsupporting
confidence: 88%
“…SUMOylation of p53 causes cellular senescence 82 , while deSUMOylation of Bmi1, a polycomb repressive complex member, is likewise, required for senescence 83 . Moreover, the SUMO E2 enzyme, Ubc9, regulates senescence by relocation of SUMOylated proteins to PML nuclear bodies 84 . Thus balanced protein SUMOylation is critical for stress resistance and survival.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins constitutively residing in PML bodies include the six nuclear PML isoforms, the speckled 100 kDa (Sp100) nuclear antigens, the death domain-associated protein (Daxx) and the small ubiquitin-like modifier (SUMO) family members SUMO1, SUMO2, SUMO3 and SUMO5 [13,14]. PML bodies are considered to be SUMOylation hubs, and most proteins associated with these organelles are post-translationally modified by one or more SUMO paralogs [12,15]. While SUMO1 attaches only as a monomer, SUMO2, SUMO3 and SUMO5 can form polymeric chains on target proteins including PML [14,16].…”
Section: Introductionmentioning
confidence: 99%